Viability of Muzara’ah Contract on Agro-financing in Alleviating Rural Poverty in Kano State, Nigeria - Bello Sani Yahuza (Department of Islamic Economics, IPB University, 2018)
The problems of inadequate sources of financing agriculture and scarcity of credit facilities to rural farmers due to interest rate and lack of collateral or guarantor to secure loans thus, many lands become fallow especially in dry season; this adversely affects the entire yield in the rural areas. Aims to assess the viability of Muzara’ah in providing sources of agro-financing and alleviating rural poverty, the study conducted in Kura LGA Kano State, adopted quantitative survey method, 152 samples out of 250 registered farmers were used as guided by Krejcie & Morgan 1970, using random sampling, questionnaire for data collection and chi-square test for goodness of fit for analysis. The paper finds the viability of muzara’ah in providing sources of agro-financing very significant as it seeks to bridge the gap that exists between the deficit and surplus landowners where the latter offered his surplus land to the former and employ his labor to till the land and share the yield on a pre-agreed ratio. The paper suggests the proper implementation of muzara’ah to cultivate more lands, generate job creation, increase farmers income earning and enhance food security which in turn alleviates rural poverty.